2015
DOI: 10.1007/s13277-015-3419-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of myeloid zinc finger 1 and the correlation to clinical aspects of oral squamous cell carcinoma

Abstract: The myeloid zinc finger 1 (MZF1) is a zinc finger transcription factor which regulates myeloid differentiation and oncogenesis. However, little information is available concerning the MZF1 expression in oral squamous cell carcinoma (OSCC) and its correlation with patients' prognosis. We detected the expression of MZF1 in 274 patients with OSCC using tissue microarrays (TMAs) and evaluated the associations between nuclear MZF1 expression and the clinical parameters of OSCC patients. We found that nuclear MZF1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Loss of nuclear expression of MZF1 has been associated with more advanced clinical stages in oral squamous cell carcinoma indicating that MZF1 can act as a negative regulator of tumorigenesis , while we observed both GABP and MZF1 have nuclear expression, and induce tumor growth through the activation of YAP1 in OS. Previous studies indicated that YAP1 may associate with promoters of genes which are important for the pluripotency of ESCs , through the mediation of the TEAD TF .…”
Section: Discussionmentioning
confidence: 53%
“…Loss of nuclear expression of MZF1 has been associated with more advanced clinical stages in oral squamous cell carcinoma indicating that MZF1 can act as a negative regulator of tumorigenesis , while we observed both GABP and MZF1 have nuclear expression, and induce tumor growth through the activation of YAP1 in OS. Previous studies indicated that YAP1 may associate with promoters of genes which are important for the pluripotency of ESCs , through the mediation of the TEAD TF .…”
Section: Discussionmentioning
confidence: 53%
“…24,27 In epidemiological studies, a reduced MZF1 expression in OSCC patients was associated with a larger tumour size and advanced clinical tumour stadium. 25 The observed tumour-specific expression patterns of MZF1 explain the cell line specific binding specificities: After the results of the TF array (data not shown), regarding the influence of CSE on MZF1 activity, the binding specificity after incubation with 10% CSE was examined. In this context, for both VEGF promoter reporter constructs, an elevated binding specificity of MZF1 was observed after CSE incubation in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…24 Interestingly, in patients with OSCC, a loss of MZF1 expression is associated with advanced stage and increased tumour size. 25 Therefore, we investigated the transcription factor MZF1 as a potential cigarette smoke regulated activator of VEGF-gene expression dependent on VEGF promoter polymorphism SNP 405.…”
Section: Introductionmentioning
confidence: 99%
“…Ko et al reported_ that negative MZF1 expression predicted a significantly poor overall survival rate in oral squamous cell carcinoma (SCC) patients [12]. Several similar studies indicated that MZF1 could act as a tumour suppressor in prostate, cervical, breast and colon cancer and T-cell lymphoma [4, 6, 7, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrated the critical function of MZF1 as a potential prognostic biomarker for oral squamous cell carcinoma [12]. Recently, Lee J H et al revealed that MZF1 is a putative transcription factor that directly binds to the core region of the SMAD4 promoter and stimulates transcriptional activity to play a role in inhibiting gastric cancer [13].…”
Section: Introductionmentioning
confidence: 99%